2021
DOI: 10.1177/21925682211033575
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Selective Single-Level Lumbar Endoscopic Unilateral Laminotomy for Bilateral Decompression of Multilevel Lumbar Spinal Stenosis and Risk Factors of Reoperation

Abstract: Study Design: Retrospective cohort study. Objectives: To investigate the usefulness of selective single-level lumbar endoscopic unilateral laminotomy for bilateral decompression (LE-ULBD) in patients with radiological multilevel lumbar spinal stenosis (LSS) and clarify the predictive factors of reoperation. Methods: A total of 128 patients who underwent LE-ULBD of radiological multilevel LSS were retrospectively examined. Single-level decompression was selected clinically and supplemented radiologically. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The position of the incision is slightly different among reports but is generally 0.5–2 cm from the midline ( 5 7 , 24 , 25 ). Endoscopic ULBD can improve surgical visualization, reduce postoperative low back pain, and shorten postoperative hospital stay ( 6 , 7 , 18 , 24 , 25 ). Some scholars have reported the utilization of unilateral biportal endoscopic ULBD, with the insertion point being more medial than that in unilateral biportal endoscopic interbody fusion (UBE) to protect facet joints, resulting in positive clinical outcomes ( 26 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The position of the incision is slightly different among reports but is generally 0.5–2 cm from the midline ( 5 7 , 24 , 25 ). Endoscopic ULBD can improve surgical visualization, reduce postoperative low back pain, and shorten postoperative hospital stay ( 6 , 7 , 18 , 24 , 25 ). Some scholars have reported the utilization of unilateral biportal endoscopic ULBD, with the insertion point being more medial than that in unilateral biportal endoscopic interbody fusion (UBE) to protect facet joints, resulting in positive clinical outcomes ( 26 ).…”
Section: Discussionmentioning
confidence: 91%
“…With advancements in lumbar endoscopic technology, endoscopic ULBD has been widely studied and applied since 2020 ( 24 ). The position of the incision is slightly different among reports but is generally 0.5–2 cm from the midline ( 5 7 , 24 , 25 ). Endoscopic ULBD can improve surgical visualization, reduce postoperative low back pain, and shorten postoperative hospital stay ( 6 , 7 , 18 , 24 , 25 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Yoshikane et al reported the efficacy of lumbar endoscopic unilateral laminotomy for bilateral decompression in the treatment of postoperative recurrence of LSS, observing excellent pr good results in 69% of the patients according to the Macnab criteria. 26 In addition, significant improvements were observed in the numerical rating scale (NRS) for low back pain, NRS-lower leg pain, NRS-lower leg numbness, and walking ability of the Japanese Orthopedic Association Back Pain Evaluation Questionnaire (JOABPEQ). In our study, the results showed that VAS leg pain score improved from 6.1±1.0 preoperatively to 2.0±1.2 postoperatively, VAS back pain score improved from 6.2±0.8 preoperatively to 2.1±1.1 postoperatively, and ODI improved from 68.9±6.0 preoperatively to 20.9±5.6 postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the clinical outcomes of interlaminar full-endoscopic laminectomy are not different from those of conventional laminectomy [ 13 15 , 19 22 ]. However, all previous studies comparing interlaminar full-endoscopic laminectomy and conventional open laminectomy are retrospective or single-center prospective studies [ 4 , 13 15 , 20 , 21 , 23 25 ]; therefore, a multicenter, randomized controlled trial (RCT) is needed.…”
Section: Introductionmentioning
confidence: 99%